CLUSTER IMPLEMENTATION OF FUNCTIONS OF REDUNDANCY MEANS - Filippova, Olga (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Various functions of redundancy means in a fiction text in most cases act in close cooperation, being implemented in a cluster. The interaction of functions is a characteristic feature of this linguistic phenomenon, which is the subject of our study. The aim of this article is to identify the functional and conceptual significance of redundancy means in a fiction text, which involves solving the following tasks:1) to determine the main methodological prerequisites of the study, based on the critical analysis of linguistic literature on the problems of cognitive linguistics, cognitive stylistics and fiction text; 2) to identify the main means of the cognitive category of redundancy in a fiction text; 3) to prove the conceptual and functional significance of the category of redundancy in a fiction text; 4) to substantiate the cluster implementation of redundancy functions in a fiction text.